“Walking with myself by my side” - non-medical use of Ketamine - R. Vaz; J. Martins; A. Costa; J. Brás; R. Sousa; E. Almeida; J. Abreu; D. Teixeira; A. Marques; N. Gil; P. Carriço (European Psychiatry, 2022)
Introduction Ketamine, synthesized in 1962 as phencyclidine derivate, is denominated a “dissociative anesthetic” because of its side-effects, such as dissociative episodes and psychotic-like symptoms, which have limited its applicability on clinical practice. Otherwise, in the last decades the non-medical use of ketamine has been growing and today is one of the most popular illicit substances consumed between adolescents and young adults.